EVANGELISASI (MALUKU) DALAM WACANA KRITIS PASCAKOLONIAL - Batlayeri, Willem (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2016)
By the phrase “post-colonial state” is not sufficently expressed the position of those former colonial-governed states. Neither is the rather “chronical” prefix “pasca” (former) in the phrase “pasca-colonialism” enough to express their situation as “after colonialism”. The phrase “pasca-kolonialism” idicates a critical interpretation of the whole cultural product which has been influenced by colonial goverment ip to now. In this context we deem it worthwile in this article to reflect on evangelization and colonialism. We do not intend to romanticize the history of colonisation, but reconstruct history in order to expose what is said about the power of simbolics and the contruction of the identity of the colonial subject that is yielded in factual discourse. Thus in fact this article is meant to be a critical reflection on any discourse on evangelization and colonialism in the Moluccas.